2013
DOI: 10.1080/09658211.2013.795973
|View full text |Cite
|
Sign up to set email alerts
|

Dying scenarios improve recall as much as survival scenarios

Abstract: Merely contemplating one's death improves retention for entirely unrelated material learned subsequently. This "dying to remember" effect seems conceptually related to the survival processing effect, whereby processing items for their relevance to being stranded in the grasslands leads to recall superior to that of other deep processing control conditions. The present experiments directly compared survival processing scenarios with "death processing" scenarios. Results showed that when the survival and dying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…In the second study reported below, we tested what we will refer to as the "life-after-death" scenario against two different survival scenarios (ancestral and modern) and a standard deep-processing control condition, namely pleasantness. We took into consideration Burns et al (2014a) criticism of Klein's (2014) dying scenario by choosing a thematic, detailed and concrete dying condition. In the life-afterdeath scenario, the participants had to imagine that they had been informed that they were about to die having just been told that there is life after death.…”
Section: Discussion Of Studymentioning
confidence: 99%
See 4 more Smart Citations
“…In the second study reported below, we tested what we will refer to as the "life-after-death" scenario against two different survival scenarios (ancestral and modern) and a standard deep-processing control condition, namely pleasantness. We took into consideration Burns et al (2014a) criticism of Klein's (2014) dying scenario by choosing a thematic, detailed and concrete dying condition. In the life-afterdeath scenario, the participants had to imagine that they had been informed that they were about to die having just been told that there is life after death.…”
Section: Discussion Of Studymentioning
confidence: 99%
“…It therefore remains unclear as to whether or not the mechanisms that underlie the DTR and survival effects overlap. As a result, and as acknowledged by Burns et al (2014a), more research on this issue is needed. The goal of our study was therefore to submit to further empirical tests the idea that the memory effects of survival and death thoughts are underpinned by similar mechanisms, and thus that the survival effect in memory is related to the activation of death thoughts.…”
mentioning
confidence: 88%
See 3 more Smart Citations